Globalization and Islam : A Case Study of Indonesian Islamic NGOs - Lawrence, Rebecca (My University, 2015)
By examining the activities of Muhammadiyah and Nahdlatul Ulama, two non-governmental organizations, I argue that globalization has not necessarily affected Islamic cultural identity negatively. Instead, Islamic organizations responded to the challenges of globalization proactively and established interconnectedness, cooperation, and tolerance.
Color poster with text, photographs, and maps.
Keywords: Non-governmental organizations (NGOs); Globalization; Islam; Posters